One in a billion: MSSM-like D-brane statistics - Gmeiner, Florian; Weigand, Timo (Journal of high energy physics, 2006)
Continuing our recent work hep-th/0411173 [http://www.arxiv.org/abs/hep-th/0411173] , we study the statistics of four-dimensional, supersymmetric intersecting D-brane models in a toroidal orientifold background. We have performed a vast computer survey of solutions to the stringy consistency conditions and present their statistical implications with special emphasis on the frequency of Standard Model features. Among the topics we discuss are the implications of the K-theory constraints, statistical correlations among physical quantities and an investigation of the various statistical suppression factors arising once certain Standard Model features are required. We estimate the frequency of an MSSM like gauge group with three generations to be one in a billion.
Gesehen am 09.01.2018